PENDIDIKAN ISLAM SOSIOKULTURAL SEBAGAI STRATEGI DALAM MENGIKIS EROSI BUDAYA DI PESISIR - Raikhan, Raikhan; Kusuma Ningtias, Ratih; Karomah , Wardatul (At- Ta'lim : Jurnal Pendidikan, 2024)
Culture is formed by values and ideas, with one of its components being the madrasah as a practice of value education. This writing is a response to the lack of attention to the significant potential of madrasah in preserving local culture through learning practices. Madrasah holds immense power in building moral fortitude to sustain culture through religious education, curriculum, and strategies. The purpose of this research is to describe and analyze the culture of Islamic religious education in coastal,the research approach is based on a qualitative method using a case study style, allowing for a profound understanding of the implementation of Islamic religious education practices in madrasahs in the Pantura region. The findings of this research indicate that the practiced methods are through sociocultural education strategies. These strategies encompass the integration of Islamic teachings and local culture in the goals of Islamic religious education, the characteristics of students and teachers, materials, strategies, and media, as well as the evaluation of educational achievements. Additionally, these strategies include the use of co-curricular and extracurricular activities as tools and media for Islamic education, along with the recognition and respect for cultural diversity and locality in the practice of Islamic education in coastal madrasahs. In this strategy, coastal madrasahs effectively utilize co-curricular and extracurricular activities as tools and media for Islamic education. Through the diversity of these activities, madrasahs create a holistic learning environment that supports the spiritual and religious development of students while grounding them in the values of local coastal culture.